How to effectively improve the ecosystem provisioning services in traditional agricultural and pastoral areas in China?. (June 2023) - Yang, Haijiang; Gou, Xiaohua; Xue, Bing; Xu, Jing; Ma, Weijing
Highlights: Grassland and farmland are the main contributors of the traditional agricultural and pastoral areas. The contribution of grassland and farmland ecosystems to provisioning services has decreased by 0.2% and 1.7% respectively. LUCC caused by human activities is the main driver of changes in grassland and farmland provisioning services. Provide solutions for the sustainable development of traditional agricultural and pastoral areas worldwide. Abstract: The provisioning services of ecosystems are fundamental for people's livelihoods, health, and survival, yet provisioning services are highly dependent on land use/cover change (LUCC), especially in fragile alpine ecosystems. In the Qilian Mountains, one of China's traditional farming and pastoral areas, changes in provisioning services are related to regional well-being. This study focuses on the multi-scale evolution, driving factors, and sustainable development strategies for providing farmland and grassland ecosystem services from 2000 to 2020. The results showed an overall upward trend in the value of providing services by grassland and cropland ecosystems over the past 20 years, increasing by US 249 million and US 67.35 million, respectively. The economic benefits of livestock products provided by grassland and agricultural products from farmland accounted for 70.5% and 29.5% of the total income of farmers and herdsmen, respectively. However, in the past 10 years, the contribution of grassland and farmland ecosystems to provisioning services has decreased by 0.2% and 1.7% respectively. The reduction of contribution will directly affect the capacity to provisioning services, which is not conducive to regional development. It is found that human factors such as policy system change, urbanization process and ideological change are the main driving factors for the change of supply services in traditional agricultural and pastoral areas, and climate change has played a certain role in promoting. In order to effectively improve the ability of traditional agricultural and pastoral areas to provide services, we put forward the development strategy of "Ecological Husbandry + Precision Agriculture (EHPA)". and promote the "Production, Learning, Scientific research and Practical application" of ecosystem services from the five aspects of ecological space, industrial layout, ecological industrial development, ecological technology and ecological policy system, so as to improve the ability of ecosystem provisioning services.